2019
DOI: 10.1002/tqem.21665
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, potentialities, and actions for implementation of sustainable energy procedures in Brazilian federal universities

Abstract: Many universities around the world have served as active centers for research on climate change.However, there are several barriers to their activities, stemming from the nature of research, resources, and the structure of institutions. This document provides an overview of barriers, potential factors, and activities to develop and implement sustainable energy processes in public higher education institutions (HEIs) in Brazil. The research was conducted from March to April of 2018 with representatives of HEIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The union between company and community, is also well regarded by managers, given their strong agreement that the results present, these issues are also presented in studies conducted by Ávila et al. (2019), Leal Filho et al. (2019), and Brandli et al.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The union between company and community, is also well regarded by managers, given their strong agreement that the results present, these issues are also presented in studies conducted by Ávila et al. (2019), Leal Filho et al. (2019), and Brandli et al.…”
Section: Resultssupporting
confidence: 75%
“…Therefore, sustainability is responsible for enhancing its environmental concepts, practices, and systems, fostering the development of the fundamental role of sustainable goals in the performance of an environmentally sustainable future (Avila et al., 2019). Thus, sustainability is well integrated into the mission and strategic objectives with the moral responsibility to spread throughout society the values and knowledge needed to create sustainable development strategies (Giovanelli et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are several challenges to be overcome [14,27]. Additionally, most of the studies found in the literature focus on sustainable practices implementation into Brazilian HEIs [28][29][30][31], instead of ESD.…”
Section: Introductionmentioning
confidence: 99%